1997
DOI: 10.1182/blood.v90.2.542.542_542_548
|View full text |Cite
|
Sign up to set email alerts
|

A Metalloproteinase Inhibitor Prevents Lethal Acute Graft-Versus-Host Disease in Mice

Abstract: Tumor necrosis factor (TNF ) and Fas ligand (FasL) have been implicated in the pathogenesis of graft-versus-host disease (GVHD), which is a major complication after allogeneic bone marrow transplantation. We examined here the ameliorating effect of a metalloproteinase inhibitor (KB-R7785) that inhibits TNF-α and FasL release in a lethal acute GVHD model in mice. Administration of KB-R7785 into (BALB/c × C57BL/6) F1 that received C57BL/6 spleen cells markedly reduced the mortality and weight loss in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…0.5% CMC vehicle was used as the control. Mice were injected subcutaneously with 2 mg per 0.2 ml of KB-R7785 or with 0.2 ml of 0.5% CMC [11].…”
Section: Mmp Inhibitormentioning
confidence: 99%
See 4 more Smart Citations
“…0.5% CMC vehicle was used as the control. Mice were injected subcutaneously with 2 mg per 0.2 ml of KB-R7785 or with 0.2 ml of 0.5% CMC [11].…”
Section: Mmp Inhibitormentioning
confidence: 99%
“…The previous study demonstrated that KB-R7785 blocks the release of TNF-K from the cell surfaces [11]. To con-¢rm that KB-R7785 would reduce the production of soluble TNF-K induced by L. monocytogenes, spleen cells obtained from naive mice were stimulated with heat-killed L. monocytogenes cells in the presence of various concentrations of KB-R7785 dissolved in 10 mM dimethylsulfoxide.…”
Section: Kb-r7785 Inhibits the Release Of Soluble Tnf-kmentioning
confidence: 99%
See 3 more Smart Citations